Fatal SARS in X-Linked Lymphoproliferative Disease Type 1: A Case Report - Ming Hin Chung; Gilbert T. Chua; Daniel Leung; Koon Wing Chan; John Nicholls; Yu Lung Lau (Frontiers in Pediatrics, 2022)
X-linked lymphoproliferative disease (XLP1) is an inborn error of immunity (IEI) with severe immune dysregulation caused by a mutation in the SH2D1A gene resulting in the absence or dysfunction of signaling lymphocytic activation molecule (SLAM)-associated protein (SAP). The severe acute respiratory syndrome (SARS) caused by SARS-coronavirus (CoV), a highly pathogenic CoV, has been shown to only cause mild diseases in Asian children. We report on a 5-year-old Nepalese boy with agammaglobulinemia and probable SARS who died of diffuse alveolar damage 22 days after admission amid the SARS outbreak. The index patient and his younger brother were genetically confirmed to have XLP1. In the current coronavirus disease 2019 (COVID-19) pandemic, most children also had mild disease only. Children with severe COVID-19 would warrant investigations for underlying IEI, particularly along the pathways leading to immune dysregulation.